2003
DOI: 10.1002/ajmg.a.20229
|View full text |Cite
|
Sign up to set email alerts
|

Relative prevalence of malformations at birth among different religious communities in Israel

Abstract: The aim of this research was to determine the relative prevalence at birth of major malformations among the different religious communities in Israel as a way to better understand their causes. We collected data on malformations present among liveborn infants in a 10-year period from the national registry of birth defects according to the religious affiliation. In a total of 1,203,763 liveborn infants, the prevalence of major malformations was in a similar range among Jews and Christians and much higher among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 6 publications
0
31
3
Order By: Relevance
“…4 -7 Not surprisingly, the prenatal incidence in Israel for almost all major malformations is higher among Druze than Jews. 8 The fact that terminating pregnancies of affected fetuses is much less common among Druze than Jews 8 results in a difference in the rate of malformations between these populations that is even greater at birth than prenatally. For example, during 1991 and 2000 the rate of Down syndrome at birth was 2.4 times higher among Druze than Jews, and the rates for anencephaly and encephalocele were more than five times higher.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 -7 Not surprisingly, the prenatal incidence in Israel for almost all major malformations is higher among Druze than Jews. 8 The fact that terminating pregnancies of affected fetuses is much less common among Druze than Jews 8 results in a difference in the rate of malformations between these populations that is even greater at birth than prenatally. For example, during 1991 and 2000 the rate of Down syndrome at birth was 2.4 times higher among Druze than Jews, and the rates for anencephaly and encephalocele were more than five times higher.…”
mentioning
confidence: 99%
“…For example, during 1991 and 2000 the rate of Down syndrome at birth was 2.4 times higher among Druze than Jews, and the rates for anencephaly and encephalocele were more than five times higher. 8 Screening of high-risk populations has proven successful and cost effective for the prevention of life-limiting AR diseases such as Tay Sachs, cystic fibrosis, and Thalassemia. 9 -12 The ultimate goal of population screening is reduction in the incidence, morbidity, and mortality of birth defects and genetic disorders.…”
mentioning
confidence: 99%
“…6,11,14 The Israeli and Palestinian populations are characterized by a relatively high rate of consanguineous marriages and marriages within specific ethnic groups, leading to a high proportion of AR diseases. 21,22 In our study, we analyzed Israeli and Palestinian families with AR retinal degenerative diseases for CRB1 mutations, and show that homozygosity mapping is a powerful tool to identify causative genes and mutations in this population.…”
mentioning
confidence: 99%
“…Various forms of congenital malformation of the central nervous system, speech and infertility were found at a higher frequency in those individuals whose parents are familyrelated, than those with unrelated parents (Bromiker et al, 2004;Zlotogora, 1997). A high proportion of infant mortality due to congenital malformation in the Arab community in Israel is mainly caused by the high frequency of consanguineous marriages (Zlotogora et al, 2003). A report published by Abu-Rabia & Maroun (2005) showed that consanguinity negatively affects children's reading abilities.…”
Section: Introductionmentioning
confidence: 99%